Macroporous Nanostructured Nb2O5 with Surface Nb4+ for Enhanced Lithium Ion Storage Properties. Issue 7 (25th May 2016) - Li, Shuang; Schmidt, Charles N.; Xu, Qian; Cao, Xi; Cao, Guozhong
Abstract: Macroporous Nb2 O5 (MP‐Nb2 O5 ) has been synthesized using dispersed polystyrene microspheres (PS) as template followed by annealing in air. The structural characterization showed that the diameters of the macropores are around 200 nm and the average particle size of the composition is 20–50 nm. XPS revealed the presence of low valence Nb 4+ and oxygen vacancies on the surface of the resulting product introduced during the pyrolysis of PS. Such a unique combination of macroporous nanostructure and tetravalent niobium ions enables the electrode with superior lithium ion insertion properties, such as high specific capacity (≈190 mA h g −1 at 0.5C) and rate capability. Even at a current density of 1.6 A g −1, an average capacity of 129.2 mA h g −1 can still be obtained. These findings demonstrate MP‐Nb2 O5 is a promising candidate for high‐rate lithium ion storage applications. Abstract : Macroporous Nb2 O5 (MP‐Nb2 O5 ) is synthesized using polystyrene microspheres (PS) as a template. The macroporous nanostructure combined with the existence of tetravalent niobium ions results in a material with enhanced electrochemical performance.